Effects of sintering profile on the densification behaviour of forsterite ceramics - Ramesh, S.; Tan, S.S.; Bang, L.T.; Tan, C.Y.; Purbolaksono, J.; Ramesh, S.; Teng, W.D. (Hanyang University Press, 2015)
The sintering behaviour of forsterite prepared by mechanical activation and heat treatment has been studied. The green compacts were sintered using two different sintering profiles. The first was based on the conventional sintering (CS) profile in which the powder compact was sintered at the desired temperature, holding for 2 hours and then cooled to room temperature. The second was based on a two-step sintering (TSS) profile in which the samples were sintered at a temperature T1 = 1400 degrees C for 6 minutes and then continued sintering at a lower temperature T2 (i.e. 750 degrees C, 850 degrees C and 950 degrees C) for 15 hours before cooling to room temperature. It was found that a minimum ball milling time of 7 h was necessary to completely eliminate secondary phases from developing in the forsterite matrix after sintering at 1400 degrees C. The sintering study indicated that the CS profile was effective in enhancing the fracture toughness of the sintered body when sintered at 1400 degrees C but this was accompanied by exaggerated grain growth. In addition, it was found that sintering below 1400 degrees C was not effective in preventing the formation of secondary phases in the sintered body. On the other hand, the TSS profile (T1 = 1400 degrees C, T2 = 950 degrees C) was found to be most beneficial in promoting densification and more importantly, to suppress grain coarsening of the forsterite body.